2014
DOI: 10.1038/ncomms5721
|View full text |Cite
|
Sign up to set email alerts
|

The unlikely Carnot efficiency

Abstract: The efficiency of an heat engine is traditionally defined as the ratio of its average output work over its average input heat. Its highest possible value was discovered by Carnot in 1824 and is a cornerstone concept in thermodynamics. It led to the discovery of the second law and to the definition of the Kelvin temperature scale. Small-scale engines operate in the presence of highly fluctuating input and output energy fluxes. They are therefore much better characterized by fluctuating efficiencies. In this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
322
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(344 citation statements)
references
References 34 publications
19
322
2
1
Order By: Relevance
“…They have computed the large deviation function for stochastic efficiency which supported the prediction given in Ref. [45]. Gingrich et al [47] computed the finite time probability density function for stochastic efficiency of a twolevel heat engine using time-asymmetric driving in a cyclic process.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…They have computed the large deviation function for stochastic efficiency which supported the prediction given in Ref. [45]. Gingrich et al [47] computed the finite time probability density function for stochastic efficiency of a twolevel heat engine using time-asymmetric driving in a cyclic process.…”
Section: Introductionmentioning
confidence: 70%
“…It captures the large time statistics of the efficiency of the stochastic engine. In a recent study, Verley et al [45] computed the large deviation function J(η) using FT for microscopic heat engine using two set of examples: work to work converter engine and a photoelectric device. They have shown that the Carnot efficiency is least likely in the long time limit, which is a remarkable result.…”
Section: Introductionmentioning
confidence: 99%
“…The larger these two variables are, the better engine we have. Traditionally [15,39,40] they are defined as η = W out /Q h and P = W out /t p , where Q h = ∆E I + W I is the amount of heat accepted by the engine from the hot reservoir.…”
Section: Power Optimization Proceduresmentioning
confidence: 99%
“…The ratio of these variables yields the efficiency which is thus itself random variable. Large deviation form of the corresponding probability distribution exhibits the following universal features [40][41][42][43][44][45][46][47][48]: (i) the most probable value of efficiency corresponds to its traditional definition using averages of work and heat, (ii) in case of time-reversal symmetric driving the least probable value of efficiency equals to η C .…”
Section: Introductionmentioning
confidence: 99%
“…The non self-averaging nature of fluctuations in stochastic efficiency and other quantities requires detailed understanding of full probability distributions as opposed to the average behavior [41,42]. Large deviation properties of such distributions are recently under theoretical investigations [45,46,47,48,49,50,51]. Research on fluctuation relations for heat engines [52,53,54] are being pursued.…”
Section: Introductionmentioning
confidence: 99%